2018
DOI: 10.1590/1678-4162-9587
|View full text |Cite
|
Sign up to set email alerts
|

Use of a GnRH synthetic analog (buserelin) for estrous induction in female dogs

Abstract: The aim of this study was to evaluate the effectiveness of a GnRH synthetic analog, as an estrous inducer in female dogs when administered during the anestrous phase, and to evaluate the pregnancy rate achieved through natural copulation. For this purpose, ten female dogs of different breeds were used. The subjects received buserelin by intramuscular injections at a dose of 2,1mcg when female dogs weighed up to 10kg (Group 1) and of 4,2mcg when the dogs weighed above 10kg (Group 2). Of the ten subjects, only t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Results revealed significantly (P˂0.05) greater number of mares, given Buserelin and Selevit in combination showed signs of estrus compared with control and those administered with Buserelin alone. These findings for estrus induction rate are in agreement with earlier reports of Rezende et al (2018) who reported administration of burserelin induce estrus in bitch during anestrus phase.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Results revealed significantly (P˂0.05) greater number of mares, given Buserelin and Selevit in combination showed signs of estrus compared with control and those administered with Buserelin alone. These findings for estrus induction rate are in agreement with earlier reports of Rezende et al (2018) who reported administration of burserelin induce estrus in bitch during anestrus phase.…”
Section: Discussionsupporting
confidence: 93%
“…In mares, the circannual rhythm of reproduction is mainly regulated by photoperiodic changes with the increase in day length preceding the onset of the breeding season (Nagy et al 2000;Kwong et al 2018). As the day light increases the pineal gland gets stimulus from the retina of eye and in response to this melatonin release will be suppressed which have negative feedback to GnRH secretion from hypothalamus, the increase secretion of GnRH from hypothalamus will trigger the gonadotropin from anterior pituitary and ultimately resumption of ovarian activity (Polasek et al 2017;Rezende et al 2018;Siemieniuch et al 2019). During winter anestrus, the extended melatonin secretion during the long periods of darkness has an inhibitory effect on GnRH secretion which leads to reduction in gonadotropin secretion, luteinizing hormone (LH) and to a lesser extent follicle-stimulating hormone (FSH) (Nagy et al 2000;Murphy 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally said that increased follicular recruitment in response to pituitary stimulation by the GnRH agonist may have contributed to the large litter size in the majority of fawns [21]. In addition, [13] eCG and hCG treatment resulted in a newborn baby with 38 whelps being reported. 29 whelps (67.3%) were alive whereas only 9 (23.7%) were lost to death.…”
Section: Resultsmentioning
confidence: 99%